Two-Way Acknowledgment-Based Trust Framework for Wireless Sensor Networks. (14th May 2013) - Anita, X.; Martin Leo Manickam, J.; Bhagyaveni, M. A.
Abstract : Security is an inherent and challenging task in Wireless Sensor Networks (WSNs) characterized by multihop routing and stringent resource constraints such as limited processing capability, storage capacity, communication bandwidth, and energy. Most of the existing trust-based routing schemes require the support of promiscuous mode of operation and gather a large number of recommendations from the neighbors for trust derivation. These result in higher energy consumption, higher communication overhead, and larger memory requirements in a resource constrained sensor network. In this paper, we propose a new two-way acknowledgment-based trust (2-ACKT) framework with individual (2-ACKT-I) and group (2-ACKT-G) acknowledgment to minimize the communication overhead and memory requirement for trust establishment in WSNs. The 2-ACKT protocol calculates the direct trust using a link layer acknowledgment and a two-hop acknowledgment from a downstream neighbor. The simulation and theoretical results indicate that 2-ACKT scheme significantly outperforms the conventional multihop and trust-based routing schemes in terms of packet delivery ratio, network lifetime, communication overhead, and memory requirements.